Impact of Macroeconomic Variabel and Global Indices on Islamic Stock Index: The Case Indonesia - Sanusi, Muhammad; Jihad, Jihad; Mawardi, Imron (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction to The Problem: The movement of the Islamic stock index can be influenced by changes in domestic macroeconomic conditions, not only domestic macroeconomics but also influenced by the stock markets of other countries.Purpose/Objective Study: The main objective of this study is to analyze the influence of the domestic macroeconomic and global stock indices on the Indonesian sharia stock index.Design/Methodology/Approach: This study uses a quantitative methodology with secondary data. The data sample method is saturated sample that all members of the population are used to be the research sample. The type of research data is monthly time series with a time period from May 2011 - July 2019, the selection of the Vactor Error Correction Model (VECM) research method based on the stationarity of the data on the first difference and the existence of cointegration models.Findings: The results showed in the short term all variables did not show a significant effect. In the long run, interest rates have a negative effect, while the exchange rate shows a positive effect on the movement of Islamic stock price indexes. Global stock indices such as the Shanghai Stock Exchange Index show a negative effect, and the Standard & Poor's 500 index shows a positive effect. While the Nikkei 225 index did not show a significant effect on the Indonesian Islamic stock index.